THE DIFFERENCE BETWEEN TOTAL DISCRETIONARY ACCRUAL BANKS WHICH HAVE ACQUIRED THE PROFIT AND LOSS IN INDONESIA - Wulandari, Ika (Accounting, 2010)
Management Earnings (earnings management) is a management action in the form of interference in the process of preparing the financial statements with the intent to improve the welfare of both individuals and companies. This study grouped samples into two groups, namely the banking company which suffered losses and banking firms gain. This study aimed to determine the indication of the presence of earnings management and the difference between the two groups of banks. Based on the results of testing using several methods showed that indeed there are indications of earnings management in both groups of banks under study. Among these two groups there were significant differences in discretionary accruals between bank profits and bank losses, which the bank makes a profit of discretionary accrualnya higher than at banks that suffered losses. Keyword : Earning Management, Total Accrual, Discretionary Accrual